Neutron autoradiography to study boron compound microdistribution in an oral cancer model - Portu, Agustina Mariana (2015)
Purpose : We previously reported the therapeutic effi cacy of Sequential Boron Neutron Capture Therapy (Seq-BNCT), i.e., BPA (boronophenylalanine) ? BNCT followed by GB-10 (decahydrodecaborate) ? BNCT 1 or 2 days later, in the hamster cheek pouchoral cancer model. We have utilized the neutron autoradiography methodology to study boron microdistribution in tissue.The aim was to use this method to evaluate if the distribution of GB-10 is altered by prior application of BPA-BNCT in Sequential BNCT protocols.Materials and methods : Extensive qualitative and quantitative autoradiography analyses were performed in the following groups: G1 (animals without boron); G2 (animals injected with BPA); G3 (animals injected with GB-10); G4 (same as G3, 24 h after BPA-BNCT); and G5 (same protocol as G4, 48 h interval).Results : A detailed study of boron localization in the diff erent tissue structures of tumor, premalignant and normal tissue in the hamster cheek pouch was performed. GB-10 accumulated preferentially in non-neoplastic connective tissue, whereas for BPA neoplastic cells showed the highest boron concentration. Boron distribution was less heterogeneous for GB-10 than for BPA. In premalignant and normal tissue, GB-10 and BPA accumulatedmostly in connective tissue and epithelium, respectively.Conclusions : BPA-BNCT could alter boron microlocalization of GB-10 administered subsequently. Boron targeting homogeneity is essential for therapeutic success.